2018
DOI: 10.4103/njo.njo_38_17
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of ocular abnormalities among students attending schools for the hearing impaired in Ibadan, South-West Nigeria

Abstract: Background: Vision screening and detection of ophthalmic disorders in hearingimpaired individuals is important to optimise their visual function and therefore, their quality of life. Objective: To determine the utilisation of eye care services among students attending schools for the hearing impaired in Oyo State, Nigeria. Methods: This was a descriptive cross-sectional study conducted among hearingimpaired students aged 11 years and above. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The limitation of Omolase et al study is that they classified visual impairment for the right and left eyes instead using the better-seeing eye. Another study conducted in Nigeria by Majekodunmi et al, 37 in 2018, reported that 56.1% of the learners had visual problems and 34.6% had visual impairment. The participants included 58.2% male and 41.8% female learners.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The limitation of Omolase et al study is that they classified visual impairment for the right and left eyes instead using the better-seeing eye. Another study conducted in Nigeria by Majekodunmi et al, 37 in 2018, reported that 56.1% of the learners had visual problems and 34.6% had visual impairment. The participants included 58.2% male and 41.8% female learners.…”
Section: Resultsmentioning
confidence: 96%
“…However, female learners with disabilities encounter an inequitable primary and secondary education as the African society values education for the boy-child than the girl-child. 37,42 The prevalence of ocular morbidity was high (20.9-73.26), which can remain undetected and impact the learners' academic pursuits. The high prevalence can be reduced through periodic eye screening, better screening protocols amongst the learners, and awareness of eye health among caretakers such as parents and teachers since these learners rely primarily on visual cues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These variations may be partly due to differences in the operational definition for classification of refractive errors, partly due to geographical location where the studies were conducted, and partly from the age distribution of the study participants. Majekodunmi et al, (2018) [26], reported that only 7.5% of their subjects with refractive errors had spectacles corrections which they got from clinics outside their school. This may likely be due to the fact that their parents may have been overwhelmed with the other challenges of their primary disability and had no clue to the possibility of ocular problems.…”
Section: Fig 1disability Status Of Participantsmentioning
confidence: 99%